Measuring High School Students’ Reading Literacy: A Case Study in North Kalimantan Province - Sukma, Bayu Permana; Prayoga, Reza Amarta; Amanat, Tri; Okitasari, Indah; Hendrastuti, Retno; Quinones Jr., Rolando P.; Rahman, Tyka (Southeast Asian Language and Literature Studies, 2025)
Reading is a fundamental tool for gleaning information and engaging in many fields of literacy. However, poor reading outcomes among Indonesian students on the PISA test indicate a low literacy level. The reading ability referred to in this study is the ability to understand reading texts on various topics and forms. This study used a sample of 234 students from eight schools in North Kalimantan Province. The data were obtained from reading tests carried out by students via computers. The test consists of 40 multiple-choice questions, short answers, and essays. The data was processed in several stages, including data reduction and item calibration using the Rasch Model. Apart from reading tests, data were also obtained through questionnaires to gather information about literacy activities carried out by students at school and at home. The results showed that nationally the average reading literacy ability of students in North Kalimantan Province was at a low level, namely at score 349, while the highest reading literacy ability average score in Indonesia was 489. The results also showed that there was a relationship between students' reading literacy skills and their conditions and habits at home. As a recommendation, students need to be more accustomed to reading multimodal texts through multimedia devices. It is important to make them capable of understanding texts containing not only words, but also pictures, numbers, graphs, and tables as demands for modern literacy. Moreover, parents also need to be to encourage to help improve the students’ literacy capacity.